2021
DOI: 10.3390/ijms222011180
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Microglia/Macrophages as a Predictor for Survival in Glioblastoma and Temozolomide-Induced Changes in CXCR2 Signaling with New Resistance Overcoming Strategy by Combination Therapy

Abstract: Tumor recurrence is the main challenge in glioblastoma (GBM) treatment. Gold standard therapy temozolomide (TMZ) is known to induce upregulation of IL8/CXCL2/CXCR2 signaling that promotes tumor progression and angiogenesis. Our aim was to verify the alterations on this signaling pathway in human GBM recurrence and to investigate the impact of TMZ in particular. Furthermore, a combi-therapy of TMZ and CXCR2 antagonization was established to assess the efficacy and tolerability. First, we analyzed 76 matched pri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 78 publications
1
34
2
Order By: Relevance
“…GSCs express various molecules that deliver either stimulatory or inhibitory signals during direct physical contact with tumor-infiltrating lymphocytes (TILs). The balance of these opposing signals regulates the amplitude and quality of TIL response and the aberrant activation of the inhibitory signals, also known as immune checkpoints, is a mechanism utilized by cancer cells to evade immune attacks [ 43 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…GSCs express various molecules that deliver either stimulatory or inhibitory signals during direct physical contact with tumor-infiltrating lymphocytes (TILs). The balance of these opposing signals regulates the amplitude and quality of TIL response and the aberrant activation of the inhibitory signals, also known as immune checkpoints, is a mechanism utilized by cancer cells to evade immune attacks [ 43 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…GBM (6). Chemokine signalling axes, for instance the CXCR2 signalling pathway, have been investigated in preclinical in vitro and in vivo experimental models as well as in GBM patient ex vivo samples (11,18,19,24). As CXCR2 is expressed by glioma cells as well as endothelial cells and overexpression of its ligands CXCL2 and IL8 is associated with a reduced patient survival (11,18,(25)(26)(27)(28), this signalling pathway is a feasible target for GBM therapy.…”
Section: Combining Tmz and Sb225002 Induces Changes Of Cxcr2 And Vegf...mentioning
confidence: 99%
“…Based on the studies aforementioned, combining CXCR2-antagonisation with the standard-of-care TMZ therapy appears promising. In another previous study by the authors, it was demonstrated that a combination therapy in vivo, consisting of TMZ and SB, reduced tumour volume in immunocompetent mice (19). However, little is known about the molecular changes during treatment with the combination therapy.…”
Section: Combining Tmz and Sb225002 Induces Changes Of Cxcr2 And Vegf...mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the stromal cells, TAMs are the most abundant ones and are important contributors to disease progression [ 7 , 8 ]. Previous studies showed a positive correlation between the abundance of TAMs and glioma grade and a negative correlation with survival [ 9 , 10 ]. Immunotherapies such as immune checkpoint inhibitors and CAR T cells are effective for a subset of hematological malignancies but have not shown efficacy in GBM and other solid tumors [ 11 ].…”
Section: Introductionmentioning
confidence: 99%